PEMIKIRAN FILSAFAT POLITIK ANTONIO GRAMSCI TENTANG HEGEMONI DAN IMPLIKASINYA TERHADAP RELASI NEGARA DENGAN MASYARAKAT SIPIL - Veranita Indah, Astrid (Sulesana: Jurnal Wawasan Keislaman, 2026)
The domination of the ruling class in modern political systems does not always occur through physical coercion, but rather through subtler ideological and cultural mechanisms. This study aims to analyze the concept of hegemony within Antonio Gramsci's political philosophy, describe the construction of the relationship between the state (political society) and civil society, and identify its implications for their structural relationship in contemporary political contexts. The method employed is library research with a qualitative-analytical approach through content analysis of Gramsci's primary works and reputable secondary journals published between 2021 and 2025. The findings reveal that Gramscian hegemony operates through the dialectic of consent and coercion, reinforced by the historic bloc and the role of organic intellectuals in reproducing dominant ideology. The state is conceived as stato integrale, a dialectical unity between political society and civil society whose boundaries remain fluid and mutually permeable. Civil society simultaneously functions as an arena for hegemonic reproduction and a potential space for counter-hegemonic movements through the strategy of war of position. This study concludes that Gramsci's thought deconstructs the liberal dichotomy between state and civil society, opening an emancipatory agenda for substantive democratization. It is recommended that critical consciousness be strengthened through transformative education and the construction of an alternative historic bloc as a sustainable counter-hegemonic force.